Analisis Kualitas Fisik dari Silase Chicory dan Onggok dalam Berbagai Rasio dengan Tambahan EM4 dan Tanin Sebagai Aditif - Jauhari, Ahmad Naufal; Hidayat, Rahmat; Setiyatwan, Hendi; Mayasari, Novi; Mushawwir, Andi; Setiawan, Muhammad Ariana; Yanza, Yulianri Rizki (Jurnal Pertanian Terpadu, 2025)
Increased livestock products challenge farmers to make animal feed more efficient. The utilization of onggok as a by-product of tapioca processing that is rich in energy and chicory as a protein source forage that is ensiled with additional additives aims to improve each other's nutrient quality. This study was conducted to evaluate the results of the material mixture by observing its physical quality, including color, texture, aroma, presence of fungi, and pH value. A completely randomized design was conducted with 6 different treatments, consisting of different ratios of basic material mixtures and the addition of additives such as EM4 and tannin. The results showed that the ratio of chicory and onggok in silage had a significant effect on the color and texture of silage, but had no significant effect on the aroma and the presence of fungi. The addition of additives also significantly affects the color of silage due to the use of EM4, and has an insignificant effect on silage pH due to the addition of tannins which affect the activity of lactic acid bacteria.